"The worst time of my life": Treatment‐related stress and unmet needs of women living with infertility. Issue 5 (22nd February 2021) - Öztürk, Ruşen; Herbell, Kayla; Morton, Jamie; Bloom, Tina
Abstract: Approximately 12% of women in the United States have difficulty getting pregnant or carrying a pregnancy to term (i.e., infertility). Infertility permeates women's lives and is psychologically, socially and financially burdensome. This study aimed to describe women's experiences regarding infertility and explore factors that women find helpful to alleviate their fertility‐related stressors. Using purposive sample, we conducted in‐depth qualitative interviews with infertile women. Participants reported multiple infertility treatment‐related stressors including (a) difficulty accessing infertility treatment due to financial issues, geographic disparities, and healthcare provider factors; (b) challenges during infertility treatment related to painful, embarrassing, confusing treatments, side effects, and healthcare providers' failures to fully address women's needs. The stories and findings add to a body of literature that elucidate significant stressors that women encounter in their fertility journey including a desire for empathetic, understandable, and effective treatment and support, and the crucial role of healthcare providers.